Assessing and exploring the competency of prehospital emergency medical service personnel in Klang Valley, Malaysia: a mixed method approach - Nurumal, Mohd. Said; Sukonthasarn, Apichard; Wangsrikhun, Suparat; Chanpransit, Chawapornpan (Faculty of Medicine, International Islamic University Malaysia, 2014)
Introduction: The notion of competency in pre-hospital emergency medical service (EMS) personnel is mainly focused on the professional proficiency that he/she has to provide intervention outside of hospital setting. Consequently, the effectiveness of pre-hospital EMS performance very much depends upon the capability of the personnel at the scene and as well during transport to the definitive care center. The aim of this study is to appraise and explore the competency of pre-hospital care staff and provide strategies for improvement. Methods: A mixed method approach combining the qualitative and quantitative study design. Of 134 staffs only 111(82.84%) returned the questionnaire. Nine semi-structured interviews and two focus group discussions were performed. The main informants were nurses/assistant medical officers, nurse/assistant medical officer administrators, and emergency physicians. Results: From the quantitative finding on the competency of staff handling pre-hospital EMS, all had the essential knowledge and skills. However, most of them reported not having good knowledge and skills for invasive procedures (31%-61%), include giving medications (61%-66%). The qualitative information provided insight about the issues and strategies for the personnel in regards to competency. All the relevant qualitative data were merged into 5 categories relating issues and 5 categories to strategies that could affect the competency of the personnel. Conclusion: Pre-hospital EMS systems need to consider that the competency of pre-hospital EMS personnel has to come along with the responsible attitude of the staff itself, the support of medical direction, clear protocol for guiding them whenever needed, and continuous professional-development courses require them to maintain their professional proficiency. KEYWORDS: Emergency medical service, competency, nurse and assistant medical officer, mixed method research